Joint beamforming and cooperative jamming for secure transmission in multi-antenna decode-and-forward relaying sensor networks: A greedy switching strategy - Zhi Lin (International Journal of Distributed Sensor Networks, 2017)
In wireless sensor networks, sensor nodes are deployed to collect data and deliver the sensed information to a base station in a wireless manner. Due to the broadcast nature of wireless sensor communications, relay-sensor-based secure transmission remains a challenging issue. This article proposes a joint cooperative beamforming and jamming scheme in the relay wireless sensor networks, where the switching strategy from cooperative beamforming to cooperative jamming is applied to weaken the signal-to-interference-plus-noise ratio of the eavesdropper when the decoding threshold is not triggered. In particular, based on Charnes–Cooper transformation and S-procedure, semi-definite programming is constructed to solve the robust cooperative beamforming and jamming with a low implementation complexity, respectively. Additionally, we adopt the global power constraints in semi-definite programming to take full exploitation of the power at relay sensor. Finally, simulation results demonstrate the superiority of the proposed scheme in comparison with the traditional decode-and-forward robust scheme and the non-robust scheme.